Suppression of MAPK signaling in BRAF‐activated PTEN‐deficient melanoma by blocking β‐catenin signaling in cancer‐associated fibroblasts. (5th November 2017) - Zhou, Linli; Yang, Kun; Dunaway, Spencer; Abdel‐Malek, Zalfa; Andl, Thomas; Kadekaro, Ana Luisa; Zhang, Yuhang
Summary: Cancer‐associated fibroblasts (CAFs) in the tumor microenvironment have been associated with formation of a dynamic and optimized niche for tumor cells to grow and evade cell death induced by therapeutic agents. We recently reported that ablation of β‐catenin expression in stromal fibroblasts and CAFs disrupted their biological activities in in vitro studies and in an in vivo B16F10 mouse melanoma model. Here, we show that the development of a BRAF‐activated PTEN‐deficient mouse melanoma was significantly suppressed in vivo after blocking β‐catenin signaling in CAFs. Further analysis revealed that expression of phospho‐Erk1/2 and phospho‐Akt was greatly reduced, effectively abrogating the activating effects and abnormal cell cycle progression induced by Braf and Pten mutations. In addition, the epithelial–mesenchymal transition (EMT)‐like process was also suppressed in melanoma cells. Taken together, our data highlight an important crosstalk between CAFs and the RAF‐MEK‐ERK signaling cascade in BRAF‐activated melanoma and may offer a new approach to abrogate host‐dependent drug resistance in targeted therapy.